Modification and Anticancer Activity Study of Polyvinyl Alcohol Containing 1, 3, 4-thiadiazole - Ruwaidah S. Saeed (Journal of Global Pharma Technology, 2017)
Beginning from 2-amino-5-mercapto-1, 3, 4-thiadiazole a variety of new cyclic imides linked to 1, 3, 4-thiadiazole moiety. A  series of novel cyclic imides containing1,3,4- thiadiazole ring [1-6]through reaction of various cyclic anhydrides with 2-amino-5-mercapto-1,3,4-thiadiazole .Compounds [1-6]were reacted with anhydrous sodium carbonate  of distilled water as a solvent, then of chloroacetic acid was added to produce compounds [7-12].The compounds [7-12]reaction with SOCl2 in the presence of Benzene to producing the compounds [13-18].Chemical modification of Poly(vinyl alcohol) were obtained by reaction of PVA with compounds [13-18]using the Dimethyl formamide to produce compounds [19-24]. The structure of the synthesized compounds was identified by their analytical and spectral data such as, FTIR spectra, 1H-NMR. UV-Vis Spectroscopy, Thermal analysis [Differential Scanning Calorimetry (DSC), Thermo gravimetric analysis (TGA)], Scanning electron microscopy (SEM), Elemental analysis (CHNS) and Antibacterial activity screened via two types of bacteria. Anticancer activity also examined for all modified polyvinyl alcohol.Keywords: 1, 3, 4-thiadiazole, Polyvinyl alcohol, Antibacterial, Anticancer activities.